2017
DOI: 10.1039/c6tc05521d
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Si QD decoration onto a flexible polymeric electrospun nanofibrous mat for the colorimetric sensing of TNT

Abstract: UV range light was used for the facile synthesis of visible light emitting, surface-protected silicon quantum dots (Si QDs) and electrospun Nylon 6,6 nanofibrous mats were decorated with these Si QD's for selective TNT sensing application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 56 publications
0
9
0
4
Order By: Relevance
“…Electrospinning is a very promising technique for the fabrication of diverse functional nanofibers [30][31][32] as portrayed in Fig. 1a.…”
Section: Resultsmentioning
confidence: 99%
“…Electrospinning is a very promising technique for the fabrication of diverse functional nanofibers [30][31][32] as portrayed in Fig. 1a.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 Summary of electrospun nanofibrous membranes with different fluorescence materials for application in trace explosive detection [41][42][43][44][45][46][47] (color online).…”
Section: 电子转移(Electron Transfer)mentioning
confidence: 99%
“…Hence, our previous work, which investigated the formation of Si QD and decoration of Nylon 6,6-nanofiber (Nylon 6,6-NF), simply demonstrated that the mild and lightcontrolled reduction of the alkoxysilane precursor is possible for large-scale fabrication of Si QD. 1 From this perspective, high temperatures and pressure, extreme conditions, protec-tive gas environments and tedious procedures were eliminated for the surface-modified and controlled synthesis of the Si QD. [1][2][3] Interestingly, when the (3-aminopropyl)triethoxysilane (APTES) precursor is used, extremely abundant functional groups (e.g., alkoxides, hydroxides, and amine groups) in the aqueous atmosphere seem very suitable environments for progressive chemical organizations such as metal (Pd, Au).…”
Section: Introductionmentioning
confidence: 99%
“…NP attachment via -NH 2 groups or metal oxide (TiO 2 , ZnO) decoration via -OH or alkoxides because the final nanostructure behaves as a nanocoating with a thickness of only a few nanometera. 1 As one of the most studied nanomaterial fabrication techniques in recent years, electrospinning has been extensively investigated. It is possible to utilize polymeric or nanocomposite formulations with different mixtures and chemical structures.…”
Section: Introductionmentioning
confidence: 99%